1980
DOI: 10.1139/e80-038
|View full text |Cite
|
Sign up to set email alerts
|

A microfauna associated with Early Cambrian trilobites of the Callavia Zone, norther Antigonish Highlands, Nova Scotia

Abstract: Trilobites of the Callavia Zone s.1. occurring together with phosphatic fossils in the Little Hollow Formation are the first known Early Cambrian faunas from mainland Nova Scotia. The tectono-stratigraphic affinity of the northern Antigonish Highlands with less intensely deformed portions of the Avalonian Platform is indicated by: (1) the Avalonian character of the trilobites and Early Ordovician brachiopods, (2) the nature of the lithologic sequence of the Iron Brook Group, and (3) local evidence for a Hadryn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 13 publications
4
69
0
Order By: Relevance
“…By contrast, the Burgess Shale specimens of H. sparsa contain only weak traces of phosphate, and the SCFs were at most lightly mineralized: they lack a phosphatic component (although this may have been removed during diagenesis and/or laboratory processing) and, as with the Burgess Shale macrofossils, are flattened with no evidence of brittle deformation. These observations are consistent with a proposed link to Rhombocorniculum, whose seemingly high organic content [23] perhaps allowed some original pliability [29]. Overall, hallucigeniid spines seem to have had a rigid yet flexible construction, with a degree of phosphatic mineralization that may have varied between taxa.…”
Section: Construction and Growth Of Hallucigeniid Spinessupporting
confidence: 79%
“…By contrast, the Burgess Shale specimens of H. sparsa contain only weak traces of phosphate, and the SCFs were at most lightly mineralized: they lack a phosphatic component (although this may have been removed during diagenesis and/or laboratory processing) and, as with the Burgess Shale macrofossils, are flattened with no evidence of brittle deformation. These observations are consistent with a proposed link to Rhombocorniculum, whose seemingly high organic content [23] perhaps allowed some original pliability [29]. Overall, hallucigeniid spines seem to have had a rigid yet flexible construction, with a degree of phosphatic mineralization that may have varied between taxa.…”
Section: Construction and Growth Of Hallucigeniid Spinessupporting
confidence: 79%
“…According to Steiner et al (2007), the P. subangulata range Zone of the Qiongzhusian of South China appears to correlate with the P. lorenzi Zone of the middle-late Atdabanian of the Siberian Platform. Furthermore, the occurrence of P. subangulata, R. cancellatum, and M. effusum indicates a correlation with the Camenella baltica Zone of Avalonia and Newfoundland (Landing et al, 1980;Hinz, 1987;Landing, 1988). The occurrence of Pelagiella aff.…”
Section: Discussionmentioning
confidence: 89%
“…It has already been reported that Rhombocorniculum sclerites grew continuously by basal-internal accretion (Landing et al 1980;Landing 1995) and contain canals oriented oblique to the wall surface . Co-occurrence of dextral and sinistral sclerites of R. cancellatum suggests a bilaterally symmetrical animal, whereas the slender and broad elements probably represented distinct sclerite types within a scleritome.…”
Section: Rhombocorniculum Insolutum Missarzhevsky Inmentioning
confidence: 94%
“…In the material from the Malaya and Bol'shaya Kuonamka rivers, R. cancellatum occurs within the Judomia Zone of the Atdabanian Stage. R. cancellatum occur in Series 2 of Kazakhstan (Missarzhevsky and Mambetov 1981), South and North China Steiner et al 2007), Australia (Gravestock et al 2001), Avalonia (Landing et al 1980;Hinz 1987), and the Mediterranean region (Elicki 2005(Elicki , 2007. Missarzhevsky and Mambetov, 1981 Figs.…”
Section: Phylum and Class Uncertainmentioning
confidence: 99%